Steady-state motions for systems of rigid bodies connected with strings (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1993)
Steady-state motions for systems of rigid bodies with dynamical axes of symmetry (Lagrange's gyroscopes) interconnected by means of absolutely flexible strings are found through the use of general equations of motions, derived by the authors in [5] in an invariant tensor form.